2004
DOI: 10.1161/01.res.0000126497.38281.23
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte-Specific Overexpression of Nitric Oxide Synthase 3 Improves Left Ventricular Performance and Reduces Compensatory Hypertrophy After Myocardial Infarction

Abstract: Abstract-Nitric oxide (NO) is an important modulator of cardiac performance and left ventricular (LV) remodeling after myocardial infarction (MI). We tested the effect of cardiomyocyte-restricted overexpression of one NO synthase isoform, NOS3, on LV remodeling after MI in mice. LV structure and function before and after permanent LAD coronary artery ligation were compared in transgenic mice with cardiomyocyte-restricted NOS3 overexpression (NOS3-TG) and their wild-type littermates (WT). Before MI, systemic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
150
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(156 citation statements)
references
References 46 publications
5
150
0
1
Order By: Relevance
“…A significant increase in cell width was measured in vacuolated CM's and in CM's of the adjacent non-infarcted regions in comparison with the CM's of the remote zone. This observation is consistent with the findings of myocyte hypertrophy in non-infarcted myocardium of small animals after coronary ligation [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…A significant increase in cell width was measured in vacuolated CM's and in CM's of the adjacent non-infarcted regions in comparison with the CM's of the remote zone. This observation is consistent with the findings of myocyte hypertrophy in non-infarcted myocardium of small animals after coronary ligation [25,26].…”
Section: Discussionsupporting
confidence: 92%
“…The importance of the CNP/NPRB axis is furthermore illustrated by a series of studies about nitric oxide synthase, supporting the concept that cGMP, a second messenger not stimulated by interaction of CNP with NPRC, is a key player in the local regulation of cardiac remodelling and function after myocardial infarction [36][37][38][39].…”
Section: Discussionmentioning
confidence: 72%
“…A study found that, after chronic pressure overload, NOS3 Ϫ/Ϫ mice had increased hypertrophy, fibrosis, and contractile dysfunction compared with WT mice (41). In addition, mice with cardiac myocyte-specific NOS3 overexpression had limited hypertrophy and contractile dysfunction after pressure overload and myocardial infarction (10,23). Furthermore, it is known that I Ca plays a role in hypertrophy (14).…”
Section: Nos3 and Arrhythmogenesismentioning
confidence: 99%
“…For example, mice with specific knockout of NOS3 (NOS3 Ϫ/Ϫ ) have an increased response to ␤-AR stimulation (4,11,19,20,47). Similarly, transgenic mice with cardiac myocyte-specific NOS3 overexpression have a decreased response to ␤-AR stimulation (9,23). Although the vast majority of studies found the above effects, it should be noted that a few studies observed dissimilar results (29,46).…”
mentioning
confidence: 99%